Exploring undergraduate students mental representation and its correlation with information processing and their knowledge in learning plant transport using diagram convention. Issue 2 (February 2019) - Komalasari, I; Rahmat, A; Rahman, T
Abstract: Application of diagram convention in learning helps students to understand biological concepts. This diagram is integrated in formation of facts of a concept. The aim of this study was to analyze the correlation between mental representation (MR) of undergraduate students when reading diagram convention with information processing and their knowledge. The 27 participants consist of undergraduate students of biology education in Bandung who are studying plant transport. MR data in form of causal network is obtained through worksheet instrument developed based on CNET protocol while information processing and knowledge through an essay instrument. There's a strong correlation between MR with information processing (r = 0.578; p < 0.05) and MR with knowledge (r = 0.679; p < 0.05). This result indicates that to represent a diagram being studied requires knowledge as a bridge to connect the information contained in the diagram. Important information in diagram is processed in working memory to form causal interactions between information elements and emerge in form of causal network. Two MR patterns are found namely linear (Markov chain) and simple branching (feedback control with a single measurement). Differences in MR patterns indicate the ability of students understand the information contained in the diagram.